2019
DOI: 10.14814/phy2.14272
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of TRPM7 as a Ca2+influx pathway in adipocytes

Abstract: In adipocytes, intracellular Ca2+ and Mg2+ modulates physiological functions, such as insulin action and the secretion of adipokines. TRPM7 is a Ca2+/Mg2+‐permeable non‐selective cation channel. TRPM7 mRNA is highly expressed in adipose tissue, however, its functional expression in adipocytes remains to be elucidated. In this study, we demonstrated for the first time that TRPM7 was functionally expressed in both freshly isolated white adipocytes and in 3T3‐L1 adipocytes differentiated from a 3T3‐L1 pre‐adipocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…5 G), indicating a reduction in the total Ca 2+ mobilization due a faster inactivation kinetics after stimulation. Similarly, Inoue et al, [50] showed that naltriben (50 μM) increases a TRPM7-like current and [Ca 2+ ] cyt in adipocytes, that they associated with changes in Ca 2+ clearance. This suggests that naltriben (50-100 μM) may affect clearance mechanisms (PMCAs or Na + /Ca 2+ exchangers).…”
Section: Discussionmentioning
confidence: 79%
“…5 G), indicating a reduction in the total Ca 2+ mobilization due a faster inactivation kinetics after stimulation. Similarly, Inoue et al, [50] showed that naltriben (50 μM) increases a TRPM7-like current and [Ca 2+ ] cyt in adipocytes, that they associated with changes in Ca 2+ clearance. This suggests that naltriben (50-100 μM) may affect clearance mechanisms (PMCAs or Na + /Ca 2+ exchangers).…”
Section: Discussionmentioning
confidence: 79%
“…In adipocytes, cytosolic Ca 2+ regulates insulin responses and the secretion of adipokines. Inoue et al [ 118 ] investigated whether TRPM7 contributes to Ca 2+ influx in freshly isolated white adipocytes and in 3T3-L1 adipocytes differentiated from 3T3-L1 pre-adipocyte cells. The authors used NS8593 together with FTY720, naltriben and siRNA techniques to show that the TRPM7 channel is functionally expressed in adipocytes.…”
Section: Ns8593 As a Tool To Investigate The Function Of Trpm7 Curmentioning
confidence: 99%
“…The authors used NS8593 together with FTY720, naltriben and siRNA techniques to show that the TRPM7 channel is functionally expressed in adipocytes. The authors conclude that TRPM7 plays a role as a Ca 2+ influx pathway in adipocytes [ 118 ].…”
Section: Ns8593 As a Tool To Investigate The Function Of Trpm7 Curmentioning
confidence: 99%
“…Because the extracellular Mg 2+ produces voltage-dependent pore block, the inward current is very small in the presence of physiological extracellular divalent cations. Therefore, in our previous studies on overexpressed mouse TRPM7 (mTRPM7) current in HEK293 cells and an endogenous TRPM7 current in mouse white adipocytes, the extracellular divalent cations were eliminated to investigate the effect of oxidative stress that was induced by H 2 O 2 on both the outward and inward currents (Inoue et al, 2014; Inoue et al, 2019). H 2 O 2 was shown to inhibit TRPM7 current in a voltage-independent and an intracellular free Mg 2+ concentration ([Mg 2+ ] i )-dependent manner.…”
Section: Resultsmentioning
confidence: 99%